Sharing as a model for understanding division. Issue 11 (1st August 2018) - Ellis, Alexa; Hu, Xiaosu; Smith, Craig E.; Davis-Kean, Pamela E.; Kovelman, Ioulia
Abstract : Emerging research suggests that children's ability to divide is the best predictor of later arithmetic development. Although division is typically taught around grade 3, children much younger than this practice division when sharing and allocating resources (e.g. sharing food). To test the hypothesis that social sharing abilities are linked to the emergence of complex numerical division abilities, we examined sharing and division abilities in adults and children. The first study used functional near infrared spectroscopy to examine the neurocognitive bases of division in adults ( N =28; age range: 18–23 years) during a task that evaluated their judgment of proportions in the context of sharing, as well as traditional numerical division tasks. The second study explored the relation between sharing and emergent math abilities in children ( N =53; age range: 4–6 years) using the same sharing task and established math measures. Our findings suggest that social sharing activities might engage similar cognitive mechanisms that support mathematical reasoning. The study informs theories of numerical cognition and highlights the importance of examining gaps in how early life activities support cognitive development.